Post-producción de audio para el vídeo juego "For honor" (2017)
The thesis was developed during the months of January to May 2017, this is a Post-Production Audio project for an audiovisual short. For this video project of 7-minute, the movie trailer of the medieval videogame "FOR HONOR" was chosen. From absolute silence, all the sound design was developed, such as swords, shouts, clashes, explosions and other effects, and the original music was composed by myself for the project.